Communities of ectoparasites associated with cricetid rodents in Pereyra Iraola Biosphere Reserve, Argentina, with an analysis of Rickettsia infection = Comunidades de ectoparásitos asociados a roedores cricétidos en la Reserva de Biósfera Pereyra Iraola, Argentina, con un análisis de la infección por Rickettsia - Melis, Mauricio E.; Espinoza Carniglia, Mario V.; Paolocá, Iván; Savchenko, Ekaterina; Costa, Mariel D.; Balcazar, Dario Emmanuel; Galliari, Carlos A.; Nava, Santiago; Lareschi, Marcela (Sociedad Entomológica Argentina, 2025)
Cricetid rodents are associated with ectoparasites, which are components of biodiversity. They may also cause diseases and act as potential vectors of microorganisms. The Pereyra Iraola Park (PPI) is situated in the area of greatest biodiversity of Buenos Aires Province. Our goal was to characterize the communities of ectoparasites associated with cricetids from the Ecological Santa Elena Farm, situated at the PPI, and to analyze the presence of Rickettsia spp. in these arthropods. Samplings were conducted during 2017-2018. A subsample of ectoparasites was prepared and identified with the optical microscope, and others were subjected to molecular analysis using the PCR technique in search of Rickettsia spp. A total of 106 cricetids were trapped, and 865 ectoparasites were collected. Mesostigmata mites presented the highest richness and diversity of species, abundance and prevalence; fleas presented higher values than ticks. These results agree with researches from nearby localities. Only the fleas Polygenis (P.) atopus (Jordan & Rothschild) and Polygenis (P.) a. axius (Jordan & Rothschild) were positive for Rickettsia, with sequences corresponding to Rickettsia felis, while mites and ticks were negative. The results obtained contribute to the knowledge of the biodiversity of the PPI and to the zoonotic importance of its fauna.